Preschoolers' Recall of Science Content From Educational Videos Presented With and Without Songs. - Schechter, Rachel. (2017)
Abstract: This experimental investigation evaluated the impact of educational songs on a child's ability to recall scientific content from an educational television program. Preschoolers' comprehension of the educational content was examined by measuring children's ability to recall the featured science content (the function of a pulley and its parts) and their use of the precise scientific terms presented in the episode. A total of 91 preschoolers were included (3-5 years old). Clusters of children were randomly assigned to a control group or one of three video groups: (a) Dialogue Only, which did not include a song; (b) Dialogue Plus Lyrics, which included a song; or (c) Lyrics Only, which consisted of a song, played twice. Results from interviews suggested that children from all video groups (lyrics and/or dialogue) were able to explain the form and function of a pulley better than the control group. The data suggested that children from the Lyrics Only group understood the science content because of the visual imagery, not through the information provided in the lyrics. In terms of precise vocabulary terms, significantly more children in the Dialogue Only group recalled at least one precise term from the program compared to the Lyrics Only group. Looking at the interview as a whole, the children's responses suggested different levels of scientific understanding. Children would require additional teacher-led instruction to deepen their scientific understanding and to clarify any misconceptions. This paper discusses implications of these findings for teachers using multi-media tools in the science classroom and producers creating new educational programming for television and other platforms.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Child Development.; Advisor: Calvin Gidney.; Committee: Julie Dobrow, Elizabeth Bachrach, and Brian Gravel.; Keywords: Educational technology, Music, and Science education.